2008
DOI: 10.1007/s11427-008-0076-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genetic diversity and phylogenetic relationships among red jungle fowls and Chinese domestic fowls

Abstract: Genetic diversity and phylogenetic relationships among 568 individuals of two red jungle fowl subspecies (Gallus gallus spadiceus in China and Gallus gallus gallus in Thailand) and 14 Chinese domestic chicken breeds were evaluated with 29 microstaellite loci, the genetic variability within population and genetic differentiation among population were estimated, and then genetic diversity and phylogenetic relationships were analyzed among red jungle fowls and Chinese domestic fowls. A total of 286 alleles were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
13
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 10 publications
8
13
3
Order By: Relevance
“…The present observation of nine polymorphic microsatellite loci out of ten, with an average allele number per locus of 3.000 ± 1.4142 was more than in the report by ARYA (2012), who observed nine polymorphic loci out of 47 microsatellite loci using 3.4% MetaPhor Agarose in a high and low egg production sub-population of White leghorn chicken, but comparable to that of DESHMUKH et al, (2015), who reported 17 polymorphic loci out of 25 microsatellite loci in different chicken breeds using 3.4% MetaPhor Agarose. The allele number and average number of alleles per locus in the present study were lower than earlier reports in various native and exotic chicken breeds (PANDEY et al, 2002;VIJH and TANTIA, 2004;PANDEY et al, 2005;BAO et al, 2008;CHATTERJEE et al, 2010b). The wide variation in numbers and sizes of alleles in the pure selected strain of RIR chicken studied could be attributed to the differences in the genetic architecture of the genomes analyzed, and also may be due to loss or fixation of alleles during its long-term selection.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…The present observation of nine polymorphic microsatellite loci out of ten, with an average allele number per locus of 3.000 ± 1.4142 was more than in the report by ARYA (2012), who observed nine polymorphic loci out of 47 microsatellite loci using 3.4% MetaPhor Agarose in a high and low egg production sub-population of White leghorn chicken, but comparable to that of DESHMUKH et al, (2015), who reported 17 polymorphic loci out of 25 microsatellite loci in different chicken breeds using 3.4% MetaPhor Agarose. The allele number and average number of alleles per locus in the present study were lower than earlier reports in various native and exotic chicken breeds (PANDEY et al, 2002;VIJH and TANTIA, 2004;PANDEY et al, 2005;BAO et al, 2008;CHATTERJEE et al, 2010b). The wide variation in numbers and sizes of alleles in the pure selected strain of RIR chicken studied could be attributed to the differences in the genetic architecture of the genomes analyzed, and also may be due to loss or fixation of alleles during its long-term selection.…”
Section: Discussioncontrasting
confidence: 84%
“…In the present study, the heterozygosity at all nine polymorphic microsatellite loci varied from 0.0997 to 0.7421; the mean heterozygosity was 0.4119 ± 0.2475. The heterozygosity and PIC values observed in the present study were lower for most of the microsatellite loci as compared to the results reported earlier in different chicken populations (PANDEY et al, 2002;VIJH and TANTIA, 2004;PANDEY et al, 2005;BAO et al, 2008;CHATTERJEE et al, 2010b), which might be due to the small size of the RIR population analyzed, and it was in an extensive breeding programme, leading to either loss or fixation of some of the alleles in the course of long-term selection. The present findings are in accordance with the report by WIMMERS et al (2000), who reported lower heterozygosity (0.45) in Aseel native chicken, where the samples were taken from an organized flock and the birds were subjected to selection pressure and subsequent inbreeding.…”
Section: Discussioncontrasting
confidence: 79%
“…This study presents clear evidence that red JF and chickens have not been genetically isolated since domestication, as suggested elsewhere (35,74,115,116). Previous studies have found evidence for introgression of gray JF, which would have further altered the genetic variation present in the domestic chicken.…”
Section: The Origins Of High Diversity In Chickenssupporting
confidence: 84%
“…Wild population genetic variation at chicken immune genes that was originally captured by multiple origins and admixture (73,74) appears to have caused a trend of high diversity throughout the genes resequenced in this study. However, it does not sufficiently account for the distinctive patterns of variation observed between the cytokines and TLRs, and implies selective processes at one or both of these functional categories.…”
Section: Evolutionary Differences Between Gene Classesmentioning
confidence: 91%
“…Therefore, determining the genetic background of Yunnan domestic chicken varieties and their relationship with local Red Junglefowl could provide an improved understanding of chicken evolution and dispersal during its domestication and enable the evaluation of chicken genetic diversity and strategies for conserving its ancestral varieties. Although some local Yunnan chicken breeds have been included in genetic studies of chicken breeds using microsatellite DNA, only a few studies have discussed the diversity of Yunnan local populations in the context of their ancestral state and relationship with Red Junglefowl in remaining habitats of wild chicken populations (Qu et al, 2006;Bao et al, 2008;Li et al, 2009).…”
Section: Introductionmentioning
confidence: 99%